Rootworm resistance to Bt associated with increased injury to corn pyramids combining Bt proteins and RNA interference - Bruce E. Tabashnik; Yves Carrière (Proceedings of the National Academy of Sciences, 2025)
Crops genetically engineered to produce insecticidal proteins from the bacterium Bacillus thuringiensis (Bt) have revolutionized pest management, but their benefits have been reduced by evolution of practical resistance in at least 31 cases. To delay evolution of resistance, farmers have shifted from crops producing one Bt protein to crops called pyramids that produce two or more Bt proteins or other traits targeting each pest. Here, we focus on resistance to transgenic corn pyramids in the western corn rootworm ( Diabrotica virgifera virgifera ) and northern corn rootworm ( Diabrotica barberi ), which cost farmers in the United States $2 billion yearly in yield losses. We analyzed 998 relevant data values for 2005 to 2023 from 12 published field studies. The results support the hypothesis that rootworm resistance to Bt proteins Cry3Bb and Gpp34/Tpp35Ab reduces the efficacy of pyramids that produce one or both of these proteins and an RNA interference trait (DvSnf7) targeting rootworms, despite no apparent strong cross-resistance between the Bt proteins and DvSnf7. The reduced efficacy of pyramids producing Bt proteins and DvSnf7 entails increased root injury and emergence of adult beetles. Efficacy of DvSnf7 was substantially lower for reducing root injury than emergence. Because root injury decreases yield, the increased root injury has immediate practical consequences. More sustainable control may be achieved by deploying pyramids with traits that are each highly effective against rootworms, increasing the abundance of host plants that do not target rootworms, and combining transgenic corn with crop rotation and other control tactics in integrated pest management programs.